Consumo de cocaína y su incidencia en las relaciones afectivas de una persona de 25 años de edad en la ciudad de Babahoyo - Gualán Masache, Marjorie Isabel (2021)
The present case study dealt with cocaine consumption and its incidence in the affective relationships of a 25-year-old man, with the objective of determining cocaine consumption and its incidence in the affective relationships of a 25-year-old man in order to elaborate a treatment plan in accordance with the improvements in his family relationship. According to the results obtained based on the psychometric tests applied, it was determined that his need for consumption is medium to high, thus having a low level of affectivity with a deficit in it, he also has a medium-high level of abstinence in situations where the consumption of the substance is stopped, being related to the use of cocaine and his family problems. Addressing this issue is essential to provide information from a psychological perspective with truthfulness to society or context that is going through a similar problem, since often as a society we tend to judge the consumption of the substance from a point of view of what is consumed and not from a criterion of why, so by not knowing the background of their consumption many young people are marginalized.